The economy of small and medium business of Almaty: problems and prospects - Доскалиева, Б.; Шуленбаева, Ф.; Дарибаева, А.; Каттабеков, Е. (Journal of Economic Research & Business Administration, 2017)
Modern processes of globalization place new demands on quality parameters of States in international space. It is necessary to create a competitive economy that produces products demanded by consumers market. In this regard, the formation of the business environment is important. The article presents the trend of economic indicators for the small and medium business of Almaty in recent years. Of particular interest are the level of activity and employment in the enterprise, the main sources of funding and lending business. Programs to assist the segment of small and mediumsized businesses with modern and popular measures of state support were considered. Indicators of realization of city development projects were presented. SWOT-analysis of the market problems of functioning of small and medium business in Kazakhstan was completed.